Fracture network modelling for shale rocks – a case study from the Baltic Basin - Ząbek, Gabriel; Michna, Michał (Wydawnictwa AGH, 2015)
The discrete fracture network (DFN) approach offers many key advantages over conventional dual porosity approaches when the geometry and properties of discrete fractures play a significant role in geomechanics, and resource assessment (Dershowitz & Doe 1988).
Geology, Geophysics & Environment
Keywords: DFN; geometry; image